ANALISIS AGRIBISNIS SAPI POTONG SISTEM WEANER GADUH DAN SISTEM SWADANA MANDIRI PADA KELOMPOK TERNAK LIMOUSIN DI DESA ASTOMULYO KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Dian Fatma Sari; Raden Hanung Ismono; Wuryaningsih Dwi Sayekti (Lampung University, 2019)
This study aims to determine the procurement of production facilities subsystem, production subsystem and marketing subsystem in Weaner Gaduh system and Swadana Mandiri system of the Limousin livestock group. The study is conducted at Astomulyo Village of Punggur Subdistrict, Central Lampung Regency by census method in Limousin Group. The location is chosen purposively since the Limousin Group is the only cattle group that has registration number in Lampung. The research data collection is carried out in November 2017. The results of this study showed that the subsystem of production facilities for Weaner Gaduh systems was the same and Swadana Mandiri systems were generally the same, namely capital, cages and tools used. The difference was in the supply of cattles, in which young cattles in Weaner Gaduh system were obtained from PT GGL, whereas in Swadana Mandiri system were from other farmers. Fattening of cattles in both Weaner Gaduh system and Swadana Mandiri system were carried out for 3-4 months by intensive pattern maintenance. The difference was the type of feed used in Swadana Mandiri system included elephant grass (Pennisetum purpureum). The benefits obtained by Swadana Mandiri system on cash costs and total cost was 1.38 and 1.31, while for farmers Weaner Gaduh systems was 1.19 and 1.12 respectively. The beef cattle marketing system in the Weaner Gaduh system was that all products must be sold to PT GGL, while the Swadana Mandiri system had the freedom of selling beef cattle. In overall market behavior illustrated that PT GGL holded full control of fattening beef cattle in Weaner Gaduh system farmers, this indicated that the most efficient marketing channel was of Weaner Gaduh system structure. Key words: marketing subsystem, procurement of production facilities, production subsystem